Pierre Barbéris : Balzac et le mal du siècle. Contribution à une physiologie du monde moderne. T. I : 1799-1829; t. II : 1830-1833. Coll. -Biliothèque des idées », Gallimard 1970. 1988 pages. - Lund, Hans Peter (Revue Romane, 1972)
no abstr.